1994
DOI: 10.1016/s0741-5214(94)70009-5
|View full text |Cite
|
Sign up to set email alerts
|

The management of the infected aortic prosthesis: A current decade of experience

Abstract: The results of alternate approaches to the management of patients with infected aortic grafts were equivalent both in terms of perioperative mortality and morbidity rates in this group of patients. Complete excision of the aortic graft with axillofemoral bypass provided a satisfactory long-term outcome and remains the standard with which other approaches must be compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 23 publications
1
56
0
3
Order By: Relevance
“…8,11,27 In the past, the "gold standard" management of these patients was extra-anatomic bypass surgery followed by graft excision. 5,83,[92][93][94][95][96][97][98][99]111 In selected patients, that might still be the procedure of choice; however, because of the high rates of mortality and potential complications, including limb loss, numerous studies have suggested that alternative surgical options might be preferable to extra-anatomic bypass and graft excision. For patients with aortoenteric fistula caused by methicillin-sensitive S aureus or less virulent microorganisms, such as coagulase-negative staphylococci, streptococci, susceptible enterococci, or susceptible enteric gram-negative bacilli, graft excision and in situ reconstruction with either cryopreserved or fresh arterial allograft, venous autograft, or rifampin-bonded synthetic graft are reasonable.…”
Section: Graft Excision and In Situ Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,11,27 In the past, the "gold standard" management of these patients was extra-anatomic bypass surgery followed by graft excision. 5,83,[92][93][94][95][96][97][98][99]111 In selected patients, that might still be the procedure of choice; however, because of the high rates of mortality and potential complications, including limb loss, numerous studies have suggested that alternative surgical options might be preferable to extra-anatomic bypass and graft excision. For patients with aortoenteric fistula caused by methicillin-sensitive S aureus or less virulent microorganisms, such as coagulase-negative staphylococci, streptococci, susceptible enterococci, or susceptible enteric gram-negative bacilli, graft excision and in situ reconstruction with either cryopreserved or fresh arterial allograft, venous autograft, or rifampin-bonded synthetic graft are reasonable.…”
Section: Graft Excision and In Situ Reconstructionmentioning
confidence: 99%
“…4,[92][93][94][95][96][97][98][99]111 The primary reason for this recommendation is because of the risk of recurrent infection that can occur with in situ reconstruction. 4,[92][93][94][95][96][97][98][99]111 The major disadvantages of extra-anatomic bypass grafting and graft excision are as follows: (1) a 2-stage procedure is required; (2) conduit failure with amputation of lower extremities has been observed in 20% to 30% of patients; (3) blood supply is decreased with ischemia to the inferior mesenteric and internal iliac arteries; and (4) residual infection of the aortic stump with blowout occurs in 10% to 20% of patients. 4 Theoretically, the risk of recurrent infection should be lower with this procedure, because the VGI is resected with no in situ reconstruction in an infected tissue bed; however, in the meta-analysis published by O'Connor et al, 4 the infection rate was highest with this procedure, followed by rifampin-bonded, then arterial allograft, and lowest with venous autograft.…”
Section: Extensive Intra-abdominal Abscess or Gross Purulence Around mentioning
confidence: 99%
See 1 more Smart Citation
“…The standard treatment for an infected graft is surgical removal combined with extraanatomic bypass and appropriate anti biotictherapy [2][3][4][5][6]. The mortalityrateassoci ated with this classic approach varies between 23% and 64% in some series [2,4,[6][7][8].…”
Section: Niection Of An Aortic Vascular Graftmentioning
confidence: 99%
“…Die hohe Revisionswahrscheinlichkeit drückt sich in der hohen sekundären Offenheit von 65% im gleichen Zeitraum aus [5,58]. Andere Autoren berichten allerdings über deutlich günstigere Ergebnisse mit einer primären 5-Jahres-Offenheitsrate von 64-73% [58,60,70]. Der Versuch, eine infizierte Prothese allein mit lokalen Maßnahmen zu erhalten, kann bei später und umschriebener Infektion möglich, bei Patienten mit hohem OP-Risiko sinnvoll sein (s. oben).…”
Section: > Es Besteht Die Tendenz Zur Orthotopen Rekonstruktion Mit Bunclassified